Environmental regulation effect on the different technology innovation-based the empirical analysis. - Lihua Ma; Shiya Ma; Qisheng Tang; Mingmei Sun; Huizhe Yan; Xiuling Yuan; Wei Tian; Yufei Chen (PLoS ONE, 2024)
This article explores the impact mechanism of different types of environmental regulations on corporate green technology innovation (GTI). The research focuses on analyzing three types of environmental regulations: command based environmental regulation (ER1), market-oriented environmental regulation (ER2), and voluntary environmental regulation (ER3), and how they affect corporate GTI. This study selected enterprise GTI as the dependent variable and measured it by the number of applications for green invention patents and green utility model patents. The independent variables are the three types of environmental regulations mentioned above. According to data from Chinese A-share listed companies. Using benchmark regression models to analyze the impact of different environmental regulations on GTI, and constructing a moderating effect model to study the role of corporate R&D investment and government support in the process of environmental regulations affecting GTI. The results indicate that (1) ER1, ER2, and ER3 can all promote enterprise GTI, and the three environmental regulatory methods have a better synergistic effect. (2) R&D investment has a positive correlation with the relationship between ER2 and GTI, and a negative correlation with ER 3 and ER 1. (3) There are differences in the GTI performance of enterprises in different regions, ownership nature, factor density, and industry types under the influence of environmental regulations. (4) The impact of environmental regulatory policies on corporate GTI is mainly short-term. This study provides a new perspective on how environmental regulations affect corporate GTI, especially in the context of developing countries like China. The research findings emphasize the role of different types of environmental regulations in incentivizing corporate GTI, while also pointing out factors that governments need to consider when formulating environmental policies, such as regional differences and corporate characteristics, which are of great significance for promoting green development of enterprises and achieving broader sustainable development goals.